MOHAMMAD TABRANI SOEJOWITIRJTO: PERAN DALAM KONGRES PEMUDA 1925-1928 - Madhiyah, Farah Tinesia; Humaidi; Yanuardi, M. Hasmi (PERIODE: Jurnal Sejarah dan Pendidikan Sejarah, 2021)
The main purpose of this article is to discover the struggle of Mohammad Tabrani Soejowitirjto in the First Congress of Indonesian Youth and his role in initiating Indonesian (Bahasa Indonesia) as the national language to unite the nation. This research uses the historical method, according to Kuntowijoyo, which consists of five stages, namely: topic selection, source collection, verification, interpretation, and writing. The results of this study reveal the important role of Mohammad Tabrani Soejowitirjto in preparing the First Congress of Indonesian Youth without any interference from the Dutch. Artikel ini bertujuan untuk mengetahui perjuangan Mohammad Tabrani Soejowitirjto dalam Kongres Pemuda Pertama dan perannya dalam memprakarsai Bahasa Indonesia sebagai bahasa persatuan. Penelitian ini menggunakan metode historis, menurut Kuntowijoyo, yang terdiri dari lima tahap, yaitu: pemilihan topik, pengumpulan sumber, verifikasi, interpretasi, dan penulisan. Dari hasil penelitian ini menunjukkan bagaimana peran penting Mohammad Tabrani Soejowitirjto mempersiapkan Kongres Pemuda Pertama tanpa adanya gangguan dari pihak Belanda.